A comparative study on low-energy ion beam and neutralized beam modifications of naked DNA and biological effect on mutation - Sarapirom S. (2014)
DNA conformation change or damage induced by low-energy ion irradiation has been of great interest owing to research developments in ion beam biotechnology and ion beam application in biomedicine. Mechanisms involved in the induction of DNA damage may account for effect from implanting ion charge. In order to check this effect, we used both ion beam and neutralized beam at keV energy to bombard naked DNA. Argon or nitrogen ion beam was generated and extracted from a radiofrequency (RF) ion source and neutralized by microwave-driven plasma in the beam path. Plasmid DNA pGFP samples were irradiated with the ion or neutralized beam in vacuum, followed by gel electrophoresis to observe changes in the DNA conformations. It was revealed that the ion charge played a certain role in inducing DNA conformation change. The subsequent DNA transfer into bacteria Escherichia coli (E. coli) for mutation analysis indicated that the charged ion beam induced DNA change had high potential in mutation induction while neutralized beam did not. The intrinsic reason was attributed to additional DNA deformation and contortion caused by ion charge exchange effect so that the ion beam induced DNA damage could hardly be completely repaired, whereas the neutralized beam induced DNA change could be more easily recoverable owing to absence of the additional DNA deformation and contortion. © 2011 Elsevier B.V. All rights reserved.